PENGARUH FEAR OF MISSING OUT (FOMO) DAN FLASH SALE TERHADAP KEPUTUSAN PEMBELIAN DI MARKETPLACE SHOPEE (STUDI KASUS PADA GENERASI Z DI KOTA MUARA TEWEH) - Kasmun; Melda Safitri (JURNAL ILMU EKONOMI (MANAJEMEN PERUSAHAAN) DAN BISNIS, 2026)
This study aims to determine the influence of Fear of Missing Out (FoMO) and Flash Sale on purchasing decisions in the Shopee Marketplace among Generation Z in Muara Teweh City, both simultaneously and partially, as well as to identify the most dominant variable. The study used a quantitative method with a sample of 100 Generation Z Shopee users selected through accidental sampling technique. Data were collected through questionnaires and analyzed using SPSS 27.0. The results showed that FoMO and Flash Sale simultaneously and partially have a significant effect on purchasing decisions. The most dominant variable influencing purchasing decisions is Flash Sale.